1977
DOI: 10.1007/bf01918785
|View full text |Cite
|
Sign up to set email alerts
|

The alteration of the functional properties of human haemoglobin by spectrin

Abstract: Kinetic investigation by means of stopped flow techniques showed the rate of deoxygenation of haemoglobin to be slower in the presence of spectrin. At pH 7.15, the kinetic constant was 27.2 sec-1 in presence of spectrin instead of 34.3 sec-1 for haemoglobin alone. Also, equilibrium studies have revealed that the oxygen pressure for half-saturated haemoglobin decreased when spectrin was added to the reaction medium. At pH 7.35, the log (pO2)1/2 was 0.88 for haemoglobin in presence of spectrin instead of 0.93 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It was shown that spectrin can bind to Hb [50] and slightly increase the Hb-O 2 affinity [51]. The stabilizing effect of Hb on the spectrin tetramer, likewise, implies interaction between these two proteins [52].…”
Section: +mentioning
confidence: 99%
“…It was shown that spectrin can bind to Hb [50] and slightly increase the Hb-O 2 affinity [51]. The stabilizing effect of Hb on the spectrin tetramer, likewise, implies interaction between these two proteins [52].…”
Section: +mentioning
confidence: 99%